ANALISA SPASIAL SEBARAN EROSI DI DAS AIR BETUNG DENGAN METODE USLE MENGGUNAKAN GIS (Geografis Information System) - Azizah, Barrorotul; Aisah, Elpita; Ardiansyah, Didi (Universitas PGRI Semarang, 2024)
Along with rapid population growth, human needs for food also continue to increase. However, on the other hand, land as the main factor in agricultural production continues to decline both in quality and quantity. Decreased soil quality can occur due to erosion. Erosion is the process of loose soil grains from their parent in a place and the material is transported by water flow or wind. The process of erosion is determined by hydrological factors including rain intensity, topography, soil character, land cover vegetation, and land use. The Air Betung River Basin Sub-Regional Area, with high rainfall, has the potential for erosion which results in continuous scouring which can cause landslides and changes in land use. Based on this, an analysis of the distribution of erosion in the Air Betung River Sub-Watershed was carried out using the USLE method, then mapping was carried out using the Geographic Information System (GIS) system with Arch GIS. The aim of this research is to determine the distribution of erosion in the Air Betung Watershed, Pagar Alam City, then the results of this research are mapped using Arch GIS. The results of this mapping include land use maps, rainfall index maps, slope slope maps, Soil type index, soil erosivity index map. The map shows that the types of soil found in the Air Betung watershed consist of 3 types, namely, A leosol latosol cokku, A podmerkun podcokun, Yellowish Red Podsolk. The highest level of erosivity in the Air Betung watershed is 1207.5 tons/ha/year, and the lowest level is 0.155 tons/ha/year. The slope level ranges from 8 to 40%.